Regulation of Medicinal Plants for Public Health – European Community Monographs on Herbal Substances - Knöss, Werner; Chinou, Ioanna (Planta Medica, 2012)
The European legislation on medicinal products also addresses the medicinal use of products originating from plants. The objective of the legislation is to ensure the future existence of such products and to consider particular characteristics when assessing quality, efficacy, and safety. Two categories are defined: i) herbal medicinal products can be granted a marketing authorisation; and ii) traditional herbal medicinal products can be granted a registration based on their longstanding use if they are complying with a set of provisions ensuring their safe use. The Committee on Herbal Medicinal Products (HMPC) was established at the European Medicines Agency (EMA) to provide monographs and list entries on herbal substances and preparations thereof. Meanwhile, approx. 100 monographs have been published, which define a current scientific and regulatory standard for efficacy and safety of herbal substances and herbal preparations used in medicinal products. This harmonised European standard will facilitate the availability and adequate use of traditional herbal medicinal products and herbal medicinal products within the European Union. Consequent labelling shall also enable patients and health care professionals to differentiate medicinal products from other product categories like cosmetics, food supplements, and medical devices.
Keywords: HMPC; monographs; list entries; herbal medicinal product; traditional herbal medicinal product; well-established use